(untitled) (Chemical Engineering Research Bulletin, 2018)
The solubility experiment of L-alanine solution was performed in a 250ml jacketed glass crystallizer without and with amino acid additives at temperature from 15oC to 75oC by means of gravimetric method. On the whole, L-leucine additive significantly altered the solubility of L-alanine and Glycine additive caused an erratic pattern on the solubility data of L-alanine. The hydrophobic methyl side chain of L-leucine additives is believed to contribute to the formation of water clathrate in the solution which affected the interaction of L-alanine molecules in water solvent and thus modified the solubility of L-alanine. Finally, thermodynamic data analysis of L-alanine solution was extensively assessed. The negative deviation of L-alanine from the ideal solution is as a result of high solute-solvent interaction, which is due to the hydrophobicity and clathrate phenomenon of the water molecules in the solution. Chemical Engineering Research Bulletin 20(2018) 23-29